2017
DOI: 10.1007/s10549-017-4375-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of ridaforolimus, dalotuzumab, and exemestane compared with ridaforolimus and exemestane in patients with advanced breast cancer

Abstract: Purpose To evaluate whether adding humanized monoclonal insulin growth factor-1 receptor (IGF-1R) antibody (dalotuzumab) to mammalian target of rapamycin (mTOR) inhibitor (ridaforolimus) plus aromatase inhibitor (exemestane) improves outcomes in patients with estrogen receptor (ER)-positive advanced/metastatic breast cancer. Methods This randomized, open-label, phase II trial enrolled 80 postmenopausal women with high-proliferation (Ki67 index staining ≥15%), ER-positive breast cancer that progressed after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For instance, the combination of insulin like growth factor 1 receptor (IGF1R) inhibitors with semisynthetic rapamycin analogs inhibits the proliferation of breast and prostate cancers and myelomas. 60,[75][76][77] Similar encouraging results come from other growth factor receptor antagonists, including the epidermal growth factor receptor (EGFR). 78 Recently, an AKT inhibitor, perifosine, was used to treat multiple myeloma cells and potentiate the anticancer activity by combination with nanoparticle bound rapamycin.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 76%
“…For instance, the combination of insulin like growth factor 1 receptor (IGF1R) inhibitors with semisynthetic rapamycin analogs inhibits the proliferation of breast and prostate cancers and myelomas. 60,[75][76][77] Similar encouraging results come from other growth factor receptor antagonists, including the epidermal growth factor receptor (EGFR). 78 Recently, an AKT inhibitor, perifosine, was used to treat multiple myeloma cells and potentiate the anticancer activity by combination with nanoparticle bound rapamycin.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 76%
“…The PFS of the R/D/E did not improve compared to R/E, likely due to lower doses of ridaforolimus in the R/D/E arm. While there was less toxicity, the efficacy of the R/D/E regimen was poorer [280]. Taken together, rapalogs in combination with growth factor receptor inhibitors have limited efficacy.…”
Section: Co-targeting Mtorc1 and Growth Factor Signalingmentioning
confidence: 99%
“…Di Cosimo et al (2010), in a phase 1 clinical trial, have demonstrated clinical benefit in 21.7% of BC patients combining ridaforolimus (a small molecule inhibitor of mTOR) and IGF-1R antibody dalotuzumab. The combination was feasible and well tolerated and a phase 2 was initiated, but accrual was prematurely interrupted due to a higher than expected incidence of stomatitis in the treated patients (Rugo et al, 2017). Vlahovic et al have evaluated the clinical benefits of combining ganitumab, a monoclonal antibody directed versus IGF-1R, with everolimus (Ev) and panitumumab in patients with advanced cancers.…”
Section: Igf-1r and Pi3k/akt/mtor Axismentioning
confidence: 99%